Performing Objects and Theatrical Things - Schweitzer, Marlis; Zerdy, Joanne; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
This book rethinks historical and contemporary theatre, performance, and cultural events by scrutinizing and theorizing the objects and things that activate stages, venues, environments, and archives.
Keywords: Theater—History.; Performing arts; Arts; Theater; Theatre History; Performing Arts; Arts; Theatre and Performance Studies